Layout modelling of the built environment for autonomous mobile robots using Building Information Modelling (BIM) and simulation - Byers, Gareth; RazaviAlavi, SeyedReza (Modular and Offsite Construction (MOC) Summit Proceedings, 2022)
Robotics is a fast-growing technology in the construction industry, particularly in off-site construction and Modern Methods of Construction (MMC). Recent advancements in technologies have made robots more intelligent and capable of autonomously undertaking tasks. Navigation of the robots in the built environment requires analysis of robots’ sensor data, which is computationally sophisticated and time consuming. Modeling the layout of the built environment using BIM and simulation can reduce the computational burden of the sensor data analysis. This research aims to develop a method to transfer the geometry data from BIM models to virtual robots in the simulation environment, and provide the robots with priori knowledge about the built environment. This method is simple-to-use and can enhance robot navigation in terms of accuracy and efficiency. The method was implemented in a case study to demonstrate its usefulness and practicality.